[List Pasterski. Inc.:] Der Geistlichkeit und allen Gläubigen [...] - Hohenzollern, Joseph von (1776-1836). (Oliwa : [s.n.], 1836)
List Pasterski.
Keywords: Listy pasterskie -- Polska -- 19 w; Druki ulotne -- 19 w